On the dynamics of african easterly waves: their origin, propagation and interaction with the environment. - (:unkn) unknown (My University, 2009)
African Easterly Waves (AEWs) are synoptic baroclinic disturbances (wavelength 2000-5000 km; period 3-5 days) that propagate westward over West Africa in the monsoon season and display intraseasonal intermittence. This thesis work aims to investigate the question of the origin, growth and intermittence of AEWs through idealised modelling and analysis of observations. Factors such as possible precursors for the waves, and the relationship of the waves with the background environment - in particular the AEJ - and with convection are examined and discussed. A statistical climatological study is made of the relationship between the observed intraseasonal variations in the mid-tropospheric flow over West Africa, convection and AEW activity. An idealised modelling approach is also developped through the use of a dry global primitive equation model driven by a constant forcing tem derived from the observations. This model is used in a first configuration to simulate linear AEWs on a set of various fixed basic-states using the same idealised convective heating localised upstream of the AEJ as an initial trigger. It is shown that these convectively triggered AEWs are strongly influenced by the intra-seasonal variability of the environment. A second forcing configuration allows the model to simulate observed distributions of jets and transient disturbances, and explicitly represents the interactions between them. This simple GCM produces realistic intermittent AEWs that are shown to be triggered by precursors coming from the North Atlantic storm track.
Keywords: African Research